1999
DOI: 10.1523/jneurosci.19-12-05016.1999
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Learning and Anxiety by Corticotropin-Releasing Factor (CRF) and Stress: Differential Roles of CRF Receptors 1 and 2

Abstract: The differential modulation of learning and anxiety by corticotropin-releasing factor (CRF) through CRF receptor subtypes 1 (CRFR1) and 2 (CRFR2) is demonstrated. As learning paradigm, context- and tone-dependent fear conditioning of the mouse was used. Injection of CRF into the dorsal hippocampus before training enhanced learning through CRFR1 as demonstrated by the finding that this effect was prevented by the local injection of the unselective CRFR antagonist astressin, but not by the CRFR2-specific antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
328
3
11

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 382 publications
(362 citation statements)
references
References 60 publications
15
328
3
11
Order By: Relevance
“…Thus, CRA1000 and CP-154,526 counteracted the adaptive changes in some system impacted by CRF during the repeated withdrawals from ethanol. A number of earlier reports implicated CRF 1 receptors in the anxiogenic effects of CRF or stress (e.g., Heinrichs et al, 1997;Landgraf, 2001) and in the anxiolytic effects of CRF receptor antagonists (Brauns et al, 2001;Radulovic et al, 1999;Seymour et al, 2003). The present results are consistent with these reports but add a new dimension.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, CRA1000 and CP-154,526 counteracted the adaptive changes in some system impacted by CRF during the repeated withdrawals from ethanol. A number of earlier reports implicated CRF 1 receptors in the anxiogenic effects of CRF or stress (e.g., Heinrichs et al, 1997;Landgraf, 2001) and in the anxiolytic effects of CRF receptor antagonists (Brauns et al, 2001;Radulovic et al, 1999;Seymour et al, 2003). The present results are consistent with these reports but add a new dimension.…”
Section: Discussionsupporting
confidence: 92%
“…Rats received intraventricular injections of antisauvagine-30 (20 μg) or artificial cerebrospinal fluid (5 μl) 4 h into the first and second withdrawals. The dose of antisauvagine-30 was selected on the basis of published reports (Brauns et al, 2001;Radulovic et al, 1999). The rat pairs were placed in the social interaction arena 5 h after the removal of ethanol.…”
Section: Intraventricular Administration Of Antisauvagine-30mentioning
confidence: 99%
“…In support of this hypothesis, Radulovic et al reported in fact that the modulation of learning and anxiety in the mouse are regulated di erentially by CRH-R1 and 2 (Radulovic et al, 1999).…”
Section: Discussionmentioning
confidence: 85%
“…CRH-R1 and CRH-R2 have been shown to produce di erent e ects in the same murine behavioural model (Radulovic et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…In a previous study, a modest nonsignificant reduction of CRH-LI was seen in the hippocampus of FSL rats (Owens et al, 1991). Intrahippocampal injections of CRH have been shown to enhance learning in mice (Radulovic et al, 1999) and, conversely, injections of antisense CRH gene oligonucleotides impaired memory retention in rats (Wu et al, 1997). The observed decrease of CRH-LI in the hippocampus may possibly reflect aspects of the impaired learning performance and cognitive deficits, which are previously described features of the FSL rat (Yadid et al, 2000;Overstreet, 1993).…”
Section: Discussionmentioning
confidence: 69%